Rehabilitation using virtual gaming for Hospital and hOMe-Based training for the Upper limb post Stroke (RHOMBUS II): protocol of a feasibility randomised controlled trial. Issue 6 (7th June 2022) - Kilbride, Cherry; Warland, Alyson; Stewart, Victoria; Aweid, Basaam; Samiyappan, Arul; Ryan, Jennifer; Butcher, Tom; Athanasiou, Dimitrios A; Baker, Karen; Singla-Buxarrais, Guillem; Anokye, Nana; Pound, Carole; et al.
Abstract : Introduction: Upper limb (UL) rehabilitation is most effective early after stroke, with higher doses leading to improved outcomes. For the stroke survivor, the repetition may be monotonous. For clinicians, providing a clinically meaningful level of input can be challenging. As such, time spent engaged in UL activity among subacute stroke survivors remains inadequate. Opportunities for the stroke survivor to engage with UL rehabilitation in a safe, accessible and engaging way are essential to improving UL outcomes following stroke. The NeuroBall is a non-immersive virtual reality (VR) digital system designed for stroke rehabilitation, specifically for the arm and hand. The aim of the Rehabilitation using virtual gaming for Hospital and hOMe-Based training for the Upper limb post Stroke study is to determine the safety, feasibility and acceptability of the NeuroBall as a rehabilitation intervention for the UL in subacute stroke. Methods and analysis: A feasibility randomised controlled trial (RCT) will compare the NeuroBall plus usual care with usual care only, in supporting UL rehabilitation over 7 weeks. Twenty-four participants in the subacute poststroke phase will be recruited while on the inpatient or early supported discharge (ESD) stroke pathway. Sixteen participants will be randomised to the intervention group and eight to the control group. Outcomes assessed at baseline and 7 weeks include gross level of disability, arm function, spasticity, pain, fatigue and quality of life (QoL). Safety will be assessed by recording adverse events and using pain, spasticity and fatigue scores. A parallel process evaluation will assess feasibility and acceptability of the intervention. Feasibility will also be determined by assessing fidelity to the intervention. Postintervention, semistructured interviews will be used to explore acceptability with 12 participants from the intervention group, four from the usual care group and with up to nine staff involved in delivering the intervention. Ethics and dissemination: This trial has ethical approval from Brunel University London's Research Ethics Committee 25257-NHS-Oct/2020-28121-2 and the Wales Research Ethics Committee 5 Bangor (Health and Care Research Wales) REC ref: 20/WA/0347. The study is sponsored by Brunel University London. Contact: Dr Derek Healy, Chair, University Research Ethics committee (Derek.healy@brunel.ac.uk). Trial results will be submitted for publication in peer-reviewed journals, presented at national and international conferences and distributed to people with stroke. Trial registration number: ISRCTN11440079 ; Pre-results.